Co Single‐Atom Catalysts Boost Chemiluminescence. Issue 34 (28th May 2020) - Ouyang, Hui; Zhang, Lvxia; Jiang, Shan; Wang, Wenwen; Zhu, Chengzhou; Fu, Zhifeng
Abstract: Co single‐atom catalysts (SACs) with good aqueous solubility and abundant labelling functional groups were prepared in Co/Fe bimetallic metal‐organic frameworks by a facile solvothermal method without high‐temperature calcination. In contrast to traditional chemiluminescence (CL) catalysts, Co SACs accelerated decomposition of H2 O2 to produce a large amount of singlet oxygen ( 1 O2 ) rather than superoxide (O2 .− ) and hydroxyl radical (OH . ). They were found to dramatically enhance the CL emission of the luminol‐H2 O2 reaction by 1349 times, and, therefore, were employed as very sensitive signal probes for conducting CL immunoassay of cardiac troponin I. The detection limit of the target analyte was as low as 3.3 pg mL −1 . It is the first time that employment of SACs for boosting CL reactions has been validated. The Co SACs can also be employed to trace other biorecognition events with high sensitivity. Abstract : Illuminate your chemistry ! Co single‐atom catalysts with Fenton‐like catalytic activity were prepared on bimetallic metal–organic frameworks. They were found to greatly enhance luminol CL emission by accelerating decomposition of H2 O2 to produce a large amount of singlet oxygen. They can act as sensitive chemiluminescent probes for tracing biorecognition events such as immune binding (see figure).